Green Synthesis and Application of New Antioxidant 3052. Issue 1 (January 2020) - Guo, Jun-Lin; Tong, Xi-Wang; Xin, Ming; Yu, Li-Ying; Ning, Bo
Abstract: A new synthetic antioxidant, 4-methyl-2-tert-butyl-6-(4-methyl-3-tert-butyl-2-hydroxybenzyl)phenyl acrylate (3052) was developed. Using solid phosgene as green acyl chloride reagent, DMF as initiator, acrylic acid and 2246 bisphenol as raw materials, two-component synthesis of antioxidant 4-methyl-2-tert-butyl-6-(4-methyl-3-tert-Butyl-2-hydroxybenzyl)phenyl ester. The experimental results show that under the optimized reaction conditions, the yield of 4-methyl-2-tert-butyl-6-(4-methyl-3-tert-butyl-2-hydroxybenzyl) phenyl ester is 85.6%. The purity is greater than 98%. The synthesis method has mild reaction conditions, short reaction time and high yield, and is 4-methyl-2-tert-butyl-6-(4-methyl-3-tert-butyl-2-hydroxybenzyl)phenyl ester. The synthesis of 3052 antioxidants provides a new approach.